Waves and legacies: The making of an investment frontier in Niassa, Mozambique - García, Angela, Kronenburg; Meyfroidt, Patrick; Abeygunawardane, Dilini; Sitoe, Almeida (My University, 2021)
To understand how land-use frontiers emerge, we studied the actors driving investments in Niassa province, Mozambique. Our ethnographic research over 2017-2018 among commercial agriculture and forestry investors shows that successive waves of actors with different backgrounds, motives and business practices, arrived in Niassa to establish farms or plantations yet repeatedly failed. Waves come and go but leave sediments – legacies – that add up to gradually build the conditions for a frontier to emerge. The accumulation of these legacies has given rise to a new wave by actors from within the region, indicating that over time endogenous processes may replace externally-driven waves.
Keywords: investment frontier; Mozambique